Novel Bacterial Lipoprotein Structures Conserved in Low-GC Content Gram-positive Bacteria Are Recognized by Toll-like Receptor 2 - Kurokawa, Kenji (American Society for Biochemistry and Molecular Biology, 2012)
Bacterial lipoproteins/lipopeptides inducing host innate immune responses are sensed by mammalian Toll-like receptor 2 (TLR2). These bacterial lipoproteins are structurally divided into two groups, diacylated or triacylated lipoproteins, by the absence or presence of an amide-linked fatty acid. The presence of diacylated lipoproteins has been predicted in low-GC content Gram-positive bacteria and mycoplasmas based on the absence of one modification enzyme in their genomes; however, we recently determined triacylated structures in low-GC Gram-positive Staphylococcus aureus, raising questions about the actual lipoprotein structure in other low-GC content Gram-positive bacteria. Here, through intensive MS analyses, we identified a novel and unique bacterial lipoprotein structure containing an N-acyl-S-monoacyl-glyceryl-cysteine (named the lyso structure) from low-GC Gram-positive Enterococcus faecalis, Bacillus cereus, Streptococcus sanguinis, and Lactobacillus bulgaricus. Two of the purified native lyso-form lipoproteins induced proinflammatory cytokine production from mice macrophages in a TLR2-dependent and TLR1-independent manner but with a different dependence on TLR6. Additionally, two other new lipoprotein structures were identified. One is the “N-acetyl” lipoprotein structure containing N-acetyl-S-diacyl-glyceryl-cysteine, which was found in five Gram-positive bacteria, including Bacillus subtilis. The N-acetyl lipoproteins induced the proinflammatory cytokines through the TLR2/6 heterodimer. The other was identified in a mycoplasma strain and is an unusual diacyl lipoprotein structure containing two amino acids before the lipid-modified cysteine residue. Taken together, our results suggest the existence of novel TLR2-stimulating lyso and N-acetyl forms of lipoproteins that are conserved in low-GC content Gram-positive bacteria and provide clear evidence for the presence of yet to be identified key enzymes involved in the bacterial lipoprotein biosynthesis.